Importancia de la evaluacion de la intensidad de reaccion mediante la aplicacion de la tecnica de hemaglutinacion, para identificar grupos y subgrupos sanguineos del sitema abo y rh, en muestras de sangre de usuarios atendidos en el hospital de la brigada blindada galapagos, durante el periodo febrero - julio del año 2012 - Banegas Caraguay, Fulbio Adalberto (2012)
This research paper assesses the importance of interpretation of the intensity of hemagglutination reaction when interpreting the results of blood typing, two blood group systems are important: The ABO blood group system and Rh. The structures of the blood groups from the point of view chemical derived proteins, and carbohydrates, these combinations are inherited and transmitted in combination with the laws of Mendel.